Facile Preparation of Doxorubicin‐Loaded Upconversion@Polydopamine Nanoplatforms for Simultaneous In Vivo Multimodality Imaging and Chemophotothermal Synergistic Therapy. Issue 4 (3rd December 2014) - Liu, Fuyao; He, Xiuxia; Lei, Zhen; Liu, Liang; Zhang, Junping; You, Hongpeng; Zhang, Huimao; Wang, Zhenxin
Abstract : The development of biosafe nanoplatforms with diagnostic and therapeutic multifunction is extremely demanded for designing cancer theranostic medicines. Here, a facile methodology is developed to construct a multifunctional nanotheranostic that gathers five functions, upconversion luminescence (UCL) imaging, T 1 ‐weighted magnetic resonance imaging (MRI), X‐ray computed tomography (CT) imaging, photothermal therapy (PTT), and chemotherapy, into one single nanoprobe (named as UCNP@PDA5 ‐PEG‐DOX). For generating the UCNP@PDA5 ‐PEG‐DOX, a near‐infrared light (NIR)‐absorbing polydopamine (PDA) shell is directly coated on oleic‐acid‐capped β ‐NaGdF4 :Yb 3+, Er 3+ @ β ‐NaGdF4 upconverting nanoparticle (UCNP) core for the first time to form monodisperse, ultrastable, and noncytotoxic core–shell‐structured nanosphere via water‐in‐oil microemulsion approach. When combined with 808 nm NIR laser irradiation, the UCNP@PDA5 ‐PEG‐DOX shows great synergistic interaction between PTT and the enhanced chemotherapy, resulting in completely eradicated mouse‐bearing SW620 tumor without regrowth. In addition, leakage study, hemolysis assay, histology analysis, and blood biochemistry assay unambiguously reveal that the UCNP@PDA5 ‐PEG has inappreciable cytotoxicity and negligible organ toxicity. The results provide explicit strategy for fabricating multifunctional nanoplatforms from the integration of UCNP with NIR‐absorbing polymers, important for developing multi‐mode nanoprobes for biomedical applications. Abstract : NaGdF4 :Yb 3+, Er 3+ @NaGdF4 upconverting nanoparticle@polydopamine nanocomposites (UCNP@PDA) are synthesized by facile water‐in‐oil microemulsion method, which can be employed to construct multifunctional nanotheranostics. In vivo experimental results demonstrate that PEGylated upconverting nanoparticle (UCNP) with 5 nm polydopamine (PDA) shell (UCNP@PDA5 ‐PEG) presents strong contrast enhancement effects on subcutaneous colorectal tumor. After loading with doxorubicin (DOX), the UCNP@PDA5 ‐PEG‐DOX exhibits highly effective chemophotothermal synergistic therapy on colorectal tumor.